Program Inovasi Pengabdian Masyarakat: Pelayanan Komprehensif Kesehatan Ibu Hamil (GEBUKIN-Gerakan Ibu Hamil Sadar Pemeriksaan Kesehatan) di Wilayah Kerja UPDT Puskesmas Tumbang Kajamei Kabupaten Katingan Tahun 2021-2023: Community Service Innovation Program: Comprehensive Health Care for Pregnant Women (GEBUKIN-Movement of Pregnant Women Aware of Health Checks) in the Tumbang Kajamei Health Center, Katingan Regency, 2021-2023 - Shitah, Syara Al-Fajar; Astuti, Indria (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
The health program for pregnant women is one of the focuses of health services which ranks first in the 12 minimum service standards (SPM) in the health sector listed in the Republic of Indonesia Minister of Health Regulation No. 04 of 2019. In the health profile of Tumbang Kajamei Community Health Center in 2021, it was stated that K4 experienced a decline of 33% from 2018 to 2020, while for K6 services it was still recorded at 0% until mid-2021. This data is what makes innovation programs a necessity in providing health services for pregnant women. The aim of the activity: increase awareness of pregnant women and the community regarding the importance of routine examinations of pregnant women and increase visits by pregnant women K4 and K6 at the end of 2022. The method of this community service innovation program is sustainable comprehensive health services with 5 activities carried out in June 2021 -December 2022 (1 year 5 months). Implementation results: there was an increase in knowledge of pregnant women by 30%, increased visits and awareness of the community (cadres and companions of pregnant women) regarding health care for pregnant women. Conclusion: there has been an increase in public awareness, especially pregnant women, families and posyandu cadres, of the importance of complete and routine examinations of the health of pregnant women with an increase in pre-post test results during activities and an increase in visits as evidenced by the final achievement in 2022 which has increased.